Longitudinal association between fitness and metabolic syndrome: a population-based study over 29 years follow-up - Johannes Wiemann; Janina Krell-Roesch; Alexander Woll; Klaus Boes (BMC, 2024)
Abstract Objectives To examine the longitudinal associations between fitness and metabolic syndrome (MetS) in community-dwelling adults over 29 years of follow-up. Design Ongoing, population-based cohort study of adults aged ≥ 33 years at baseline residing in the city of Bad Schönborn, Germany. Methods The sample comprised 89 persons (41 females; mean age 40.1 years at baseline) who participated at baseline (in the year 1992) and 29-years follow-up (in the year 2021). Fitness (predictor variable) was assessed using 15 standardized and validated tests that measured strength, gross motor coordination, mobility/ flexibility and cardiorespiratory fitness/ endurance, and a z-transformed fitness score was calculated for analysis. MetS (outcome of interest) was assessed through five criteria related to waist circumference, blood glucose, HDL cholesterol, triglycerides, and blood pressure, and a sum score was created for analysis. We ran partial correlations to examine the association between fitness score at baseline and MetS score at 29-years follow-up, adjusted for age, sex, socio-economic status, smoking status, sleep quality, and physical activity engagement in minutes/ week. Results A higher fitness score at baseline was significantly associated with a lower MetS score indicative of better metabolic health at 29-years follow-up (r=-0.29; p = 0.011). These associations were present in participants aged ≤ 40 years (r=-0.33; p = 0.025) as well as those aged > 40 years (r=-0.43; p = 0.045). Conclusions Fitness may be a predictor of longitudinal metabolic health, and potentially also mediates previously reported longitudinal associations between physical activity and metabolic health. More research is needed to confirm these observations, and to also explore underlying mechanisms.